Sistem E-Commerce Perlengkapan Aquatic Berbasis Web dengan Payment Gateway dan Firebase Cloud Messaging - Ade Prima Krifitsky; Tri Widodo (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2025)
Sky Aquatic Store in Dukun, Magelang faces several operational challenges, including limited customer reach, error-prone manual stock management, and inefficient transaction communication. This study develops a web-based e-commerce system integrated with the Midtrans payment gateway and Firebase Cloud Messaging (FCM) to support the digitalization of micro, small, and medium enterprises (MSMEs). The system was built using React.js for the frontend, Node.js with Express.js for the backend, and MySQL as the database, employing the Agile Scrum methodology over an eight-week development cycle. Black-box testing conducted on ten test cases demonstrated a 100% success rate under both normal and abnormal conditions. The system successfully integrates multi-method payments (Virtual Account, E-wallet, and Credit Card) via Midtrans, along with FCM infrastructure for real-time notifications. The results confirm that all core features operate according to specifications with robust error handling, providing a comprehensive e-commerce solution that supports the digital transformation of aquatic equipment MSMEs. Keywords: E-commerce; Payment gateway; Firebase Cloud Messaging; REST API; Aquatic equipment   AbstrakToko Sky Aquatic di Dukun, Magelang menghadapi kendala jangkauan pelanggan terbatas, pengelolaan stok manual yang rawan kesalahan, dan komunikasi transaksi tidak efisien. Penelitian ini mengembangkan sistem e-commerce berbasis web terintegrasi dengan payment gateway Midtrans dan Firebase Cloud Messaging (FCM) untuk mendukung digitalisasi UMKM. Sistem dibangun menggunakan React.js (frontend), Node.js dengan Express.js (backend), dan MySQL (database), dengan metodologi Agile Scrum selama 8 minggu. Pengujian black-box testing terhadap 10 test case menunjukkan tingkat keberhasilan 100% pada kondisi normal dan tidak normal. Sistem berhasil mengintegrasikan payment gateway multi-metode (Virtual Account, E-wallet, Kartu Kredit) dan infrastruktur FCM untuk notifikasi real-time. Hasil pengujian membuktikan seluruh fitur utama berfungsi sesuai spesifikasi dengan error handling yang robust, menyediakan solusi e-commerce komprehensif untuk transformasi digital UMKM perlengkapan aquatic.